South Africa - Constraints to Growth in Johannesburg's Black Informal Sector : Evidence from the 1999 Informal Sector Survey - World Bank (Washington, DC, 2013)
The report is the third in a series of reports that evolved from a collaboration between the local government of the City of Johannesburg, and the World Bank in 1999-2000 on the theme of local economic development. It presents the main findings of the 1999 World Bank informal sector survey, which covered a number of mostly black informal firm owners across manufacturing, and service sectors, based on firm owners responses, and firm level data. The objectives of the study are to a) examine the characteristics, and constraints facing informal firms in Johannesburg. The government has since 1994, rested its goal of poverty, and inequality-reduction in South Africa, on private sector-led job creation, and, has made a political commitment to black empowerment, allocating resources for credit, and training, as well as other small and medium scale enterprise (SMSE) promotion programs; and, b) explore the policy implications of government assistance to the informal sector, on grounds of poverty reduction, and job creation for the poor. The merit of supporting the sector on the basis of apartheid-created racial inequality, is also examined. Based on international experience, micro-finance should focus on outreach, quality of services, and measures of financial sustainability. Issues for further research, specific to South Africa, include fiscal feasibility of micro credit, and training programs, incorporating the element of firm growth, and prospects for graduation to formal SMSE, with credit availability being contingent on successful completion of small business training.